A preservação da arquitetura moderna em cidades de pequeno porte: análise e investigação da Vila dos Operadores de Jaguara em Sacramento-MG. - Belo, Rafaela Borsato (2018)
The research examines the cultural heritage preservation in small towns and the difficulties encountered to recognize the cultural values of some archetypes (exemplars). Thus, it investigates the case of Jaguara Operators' Village whose example synthesizes the problems of the recognition of cultural heritage, coming from the architecture and urbanism of the Modern Movement, as well as the difficulties that smaller municipalities present in the recognition of this architecture and urbanism as values carriers to be safeguarded in the present time. Therefore, it aims to understand the obstacles that the demographically considered small town of Sacramento-MG presents in the recognition of a cultural heritage value and also in the effective preservation of the patrimony, considering that the Jaguara Operators' Village is not recognized as a bearer of such values, nor does it have its structure protected by any sphere of official preservation organs, been at the mercy of private investments and consequently of not responsible interventions. For this purpose, theoretical contributions were used to read the territory and the history of the Sacramento city, as well as the historical, political, economic and social context of the Jaguara Operators' Village, initially raised by the Center for Research in Theory and History of Architecture and Urbanism of the Faculty of Architecture and Urbanism and Design of the Federal University of Uberlândia. Thereby it was possible to reflect on the recognition of modern architecture and urbanism in a small town; the role of the municipal public administration in the protection of cultural heritage in the city of Sacramento; the peculiarities of the size of the city, with regard to the preservation of cultural heritage and also in the role of federal public sectors, which in this case appears in the figure of the public university.